Pharmacogenomics for Treatment Response in Patients With Stevens-Johnson Syndrome: An Updated Review - Henry Budiawan Prasetya; Irham, Lalu Muhammad; Adikusuma, Wirawan; Amukti, Danang Prasetyaning; Mazaya, Maulida; Chong, Rockie; Mutiara, Rina; Darmawi, Darmawi; Khairi, Sabiah; Sarasmita, Made Ary; Purwanto, Barkah Djaka; Harmain Siswanto, Lalu Muhammad; et al. (Scripta Medica, 2025)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are dermatological emergencies characterised by widespread epidermal necrolysis and sloughing. SJS is defined as the shedding of skin on less than 10 % of the body surface area, whereas TEN involves the shedding of skin on more than 30 %. The pathogenesis of SJS is identified by the occurrence of apoptosis of keratinocytes, which is spread throughout the body. The binding of the molecule to the human leukocyte antigen (HLA) peptide is one of the basic triggering mechanisms for SJS due to an autoimmune reaction. This study aims to predict genetic predictive markers for the prevention and pharmacological treatments of SJS/TEN. The PharmGKB website was used to gather information regarding the relationship among drugs, genes and the SJS condition. Results revealed notable gene variants (eg HLA-A, HLA-B, HLA-B, HLA-C, CYP2B6) predisposing individuals to a toxic response, instigating the SJS reaction. Implicated drugs included allopurinol, antiepileptics such as carbamazepine, lamotrigine, oxcarbazepine and phenytoin, as well as methazolamide and nevirapine, identified as potential risk factors. As a result, this study can provide information and facilitate precision medicine, which focuses on individual genetic variations as a means of prevention and treatment, enabling early prognosis and optimising patient care in preventing SJS/TEN.